Prevalence of intestinal parasitic infections and their associations with anthropometric measurements of school children in selected primary schools, Wukro town, eastern Tigray, Ethiopia - Kidane, E.; Menkir, S.; Kebede, A.; Desta, M. (Scientific Journal of Zoology, 2013)
The objective of thepresent study was to determine prevalence of intestinal parasitic infectionsand their associations with anthropometric measurements among school childrenof Wukro town, Eastern Tigray, Ethiopia. The design of the study was a cross-sectionalepidemiological investigation involving a sample population of 384 schoolchildren from grade one to grade eight in two purposively selected primaryschools located in Wukro town duringMarch-May, 2011/2012. A total of 384 fresh stool samples of school-childrenwere examined using direct wet-mount technique. The overall prevalence ofintestinal parasitic infection was 60.7% (58.2% in males and 62.8% in females).Multiple infections with two and above parasites were found in 7.5% (29) of thepositive stool samples. The prevalence of protozoan parasites, E.histolytica,G.lamblia and I.beli was 23.2%, 16.9% and 4.4%, respectively. Similarly, theprevalence of helminth infections, A.lumbricoides, Hookworm, T. trichiura,S.mansoni, E.vermicularis, H.nana and Teania saginata. was 5.7%, 3.9%, 3.1%,3.1%, 1.3%, 1% and 0.8%, respectively. The prevalence of intestinal parasiticinfections was significantly associated with some of risk factors, such asfamily size, source of water and its handling, and availability of latrines(p=0.000, p=0.003 and p=0.001, respectively). Even though there were high parasitic infections, they were notstatistically associated with somesocio-demographic factors, such as parents’ educational level, personalhygiene, life skills, awareness to parasitic infections, residence and wearingshoe or not. A significant association was found between intestinal parasiticinfections and underweight students (p=0.002). Underweight school-children(34.6%) had a higher prevalence of parasitic infection as compared with otheranthropometric indices (wasting and stunting). In summary, intestinal parasiticprotozoan infections represent a public health problem in the school-childrenof Wukro town. Local health sector and any concerned bodies should collaboratewith school health program for delivering health education to increase theknowledge, attitude and practice of school children as to how transmission ofintestinal parasitic infection is prevented such as improvement of personalhygiene and environmental sanitation, and shoe wearing habit.